Tindak Tutur Direktif Dalam Wacana Rapat Dinas Ke-RT-anDesa Sodong, Tengklik, Tawangmangu KabupatenKaranganyar Dan Implikasinya Sebagai Bahan AjarSekolah Menengah Atas - Surono, Teguh, Prof. Dr. Harun Joko Prayitno, M.Hum (2016)
This study has two objectives. (1) Describe the form directive speech acts. (2)Describe what the directive speech acts. (3) Describe the implications of the directive speech acts as teaching material High School. This research was conducted in the village of Sodong, Tengklik, Tawangmangu, Karanganyar. This research data is speech Sodong village residents who attend the meeting containing RT directive speech acts. The data source of this research all the speech contained in the discourse of the meeting RT. Data collection technique used recording methods, see, and continued with the techniques noted. Data analysis using sub-types of the fifth match is pragmatic method by means of decisive speech. The validity of the data used in this research is triangulation. This study researchers presented bendtuk and intent directive speech acts in discourse official meetings all Sodong RT Village, as well as teaching materials to implement high school. Results speech clarified by type. The form of a directive speech acts in discourse official meetings all RT Village Sodongberkecendengan using a type of request to the requested category and type requested in the categories offered. Then this research may implemented as High School instructional materials in accordance with the curriculum SBC on SK 9 containing understand information through speech. keywords: pragmatics, speech acts, directives, instructional materials